PENGARUH KOMPETENSI APARATUR PENGELOLAAN DANA DESA, PARTISIPENSI MAYARAKAT ATAS SISTEM PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Rina Malahayati; Almajid Bahri; Rila Maufira (SUAN PUBLISHER, 2026)
This study aims to analyze the effect of apparatus competence and community participation on the accountability of Village Fund management, with the internal control system as a mediating variable. A quantitative approach was employed using a survey method through questionnaires distributed to village officials and community representatives involved in Village Fund management. Data were analyzed using multiple linear regression and path analysis. The results indicate that apparatus competence and community participation have a positive and significant effect on the internal control system. Furthermore, the internal control system significantly influences the accountability of Village Fund management. Path analysis reveals that the internal control system mediates the relationship between apparatus competence, community participation, and accountability. The coefficient of determination demonstrates that the research model has strong explanatory power. This study concludes that enhancing the capacity of village officials and strengthening community participation should be integrated with an effective internal control system to achieve transparent and accountable Village Fund governance.